Corneal Cross-Linking as Treatment in Pediatric Keratoconus: Comparison of Two Protocols. (3rd November 2021) - Hed, Shira; Matlov Kormas, Ran; Shashar, Sagi; Malyugin, Boris E.; Boyko, Matthew; Knyazer, Boris
Abstract : Introduction . Keratoconus is a progressive corneal disease commonly treated by collagen cross-linking (CXL). Accelerated protocols have recently become common. This study sought to compare the outcomes of accelerated and standard CXL in terms of visual acuity, keratometry, and tomographic parameters in pediatric population. Methods . We retrospectively reviewed the files of pediatric patients who underwent standard and accelerated CXL for keratoconus in our hospital, between October 2014 and March 2018. Changes in uncorrected distance visual acuity (UCDVA), best corrected distance visual acuity (BCDVA), tomographic keratometry parameters ( K max, K steep, K flat, K mean ), and endothelial density count (EDC) were assessed before and at 6 and 12 months following treatment. The analysis included intergroup and intragroup comparisons. Results . This study included 53 eyes (44 patients). Fourteen eyes were treated with standard CXL (S-CXL, 3 mW/cm 2, 30 min), while 39 underwent accelerated CXL (A-CXL, 9 mW/cm 2, 10 min). Intergroup comparison found insignificant differences between groups, with the exception of better results for UCDVA in the S-CXL group after 12 months (P  = 0.03). In this study, there was no significant difference between the two protocols postoperatively in BCDVA, K max, K mean, pachymetry, or corneal astigmatism. Conclusion . A-CXL is as safe and effective as S-CXL for stabilizing progressive keratoconus in pediatric population. Larger-sample-size studies with a longer follow-up time are required. Considering the long-term results of 9 mW A-CXL and its safety and efficacy profile, it should be preferred to S-CXL for reducing treatment time and improving patients' comfort.